Increased lucid dreaming frequency in narcolepsy - Rak, Michael; Schredl, Michael (Sleep, 2015)
Study Objective: Nightmares are a frequent symptom in narcolepsy. Lucid dreaming, i.e., the phenomenon of becoming aware of the dreaming state during dreaming, has been demonstrated to be of therapeutic value for recurrent nightmares. Data on lucid dreaming in narcolepsy patients, however, is sparse. The aim of this study was to evaluate the frequency of recalled dreams (DF), nightmares (NF), and lucid dreams (LDF) in narcolepsy patients compared to healthy controls. In addition, we explored if dream lucidity provides relief during nightmares in narcolepsy patients. Design: We interviewed patients with narcolepsy and healthy controls. Setting: Telephone interview. Patients: 60 patients diagnosed with narcolepsy (23-82 years, 35 females) and 919 control subjects (14-93 years, 497 females) Interventions: N/A. Measurements and Results: Logistic regression revealed significant (P < 0.001) differences in DF, NF, and LDF between narcolepsy patients and controls after controlling for age and gender, with effect sizes lying in the large range (Cohen's d > 0.8). The differences in NF and LDF between patients and controls stayed significant after controlling for DF. Comparison of 35 narcolepsy patients currently under medication with their former drug-free period revealed significant differences in DF and NF (z < 0.05, signed-rank test) but not LDF (z = 0.8). Irrespective of medication, 70% of narcolepsy patients with experience in lucid dreaming indicated that dream lucidity provides relief during nightmares. Conclusion: Narcolepsy patients experience a markedly higher lucid dreaming frequency compared to controls, and many patients report a positive impact of dream lucidity on the distress experienced from nightmares.
Gesehen am 01.02.2018